Characterization and Growth Evaluation of Carbofuran-degrading Local Bacteria Isolated from Brinchang Cameron Highlands Malaysia - Umar Mustapha, Mohammed; Halimoon, Normala; Lutfi Wan Johari , Wan; Yunus Shokur, Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
The insecticide carbofuran is a broad-spectrum carbamate pesticide often used to control pests in the agricultural sector. However, despite its ability to effectively kill the insects on the farms, health-associated problems are still being reported due to its higher level of toxicity. Biodegradation is an effective method used for the removal of these compounds from the environment since previous methods using chemical processes of degradation prove to be ineffective due to the presence of highly stable bonds. Bacterial strain BRC05 isolated from the vegetable plantation area of Cameron Highlands was found to have carbofuran-degrading ability. The morphology and growth at different concentrations of carbofuran were studied. The growth of the isolate was evaluated in Carbofuran medium under stable and shaking conditions. The gram-negative, motile, and rod-shaped BRC05 shows good growth on Carbofuran medium after 12 hours of incubation. The optical densities of the isolate were more under shaking conditions and differed significantly from under static conditions. There is no significant difference (p>0.05) between growth at 25 and 50 mg/l under static conditions. At 25 mg/l under shaking conditions, the insecticide has less effect on the growth of the isolate. It was found that BRC05 could grow well and reach the largest biomass in the medium containing 25 mg/l of carbofuran and could keep active growth even in medium with high concentration of carbofuran 100 mg/l. These showed that the bacteria could grow and remove carbofuran in soils effectively and safely. The present study may provide a basis for biotreatment and bioremediation of carbofuran-contaminated soils.